2018
DOI: 10.2174/1874364101812010247
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Treatment Outcomes and Predictive Factors in Optic Neuritis

Abstract: Background:The causes, clinical presentations and treatment outcomes of optic neuritis are distinct among different populations. Early diagnosis based on clinical presentations plays an important role in treating optic neuritis patients.Objective: The study aimed to determine clinical characteristics, treatment outcomes and predictive factors of treatment outcomes in optic neuritis patients with and without demyelinating disease.Methods:A retrospective descriptive study of optic neuritis patients carried out b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 42 publications
5
17
0
Order By: Relevance
“…Notably, cohorts from China comprised the vast majority of the Asian cohorts in our study. However, relatively high seroprevalence of AQP4-IgG and/or MOG-IgG in ON has been reported in several studies (that did not however fully fulfill our inclusion criteria) from Japan, Thailand, Malaysia, and additional Chinese centers ( 74 , 77 , 86 89 ). Importantly, while population-based studies support the notion that Eastern Asian populations have a higher prevalence of NMOSD compared to Caucasian populations, MOG-IgG-associated disease does not appear to exhibit a significant racial preponderance based on data from existing hospital-based studies ( 90 ).…”
Section: Discussionmentioning
confidence: 81%
“…Notably, cohorts from China comprised the vast majority of the Asian cohorts in our study. However, relatively high seroprevalence of AQP4-IgG and/or MOG-IgG in ON has been reported in several studies (that did not however fully fulfill our inclusion criteria) from Japan, Thailand, Malaysia, and additional Chinese centers ( 74 , 77 , 86 89 ). Importantly, while population-based studies support the notion that Eastern Asian populations have a higher prevalence of NMOSD compared to Caucasian populations, MOG-IgG-associated disease does not appear to exhibit a significant racial preponderance based on data from existing hospital-based studies ( 90 ).…”
Section: Discussionmentioning
confidence: 81%
“…24 Furthermore, a study in Thailand reported that among 150 patients with optic neuritis, 58 patients (38.7%) showed NMO, 23 patients (15.3%) showed MS, and 69 patients (46.0%) showed idiopathic disease. 25 The above studies were conducted in specialized institutions, and the study populations presumably vary because of racial differences and contained a large proportion of severe cases of disease. Our present multicenter collaborative study included facilities with neuro-ophthalmologists.…”
Section: Rates Of Antieaquaporin-4 Antibodye and Antiemyelin Oligodenmentioning
confidence: 99%
“…[23][24][25][26][27] The results were also comparable to those reported in Chiangmai, which lies in northern Thailand. 28 A slight difference is that the number of MS cases was relatively higher in Chiangmai Province. In China, the most frequent etiology was idiopathic according to Zhang et al 23 Other autoimmune disorders and NMOSD were common etiologies in another Chinese series.…”
Section: Discussionmentioning
confidence: 99%